Applications of Mass Spectrometry in the Onset of Amyloid Fibril Formation: Focus on the Analysis of Early-Stage Oligomers - Hu, Jiaojiao; Zheng, Qiuling (Frontiers in Chemistry, 2020)
Amyloid fibril formation is a hallmark of diverse neurodegenerative and metabolic diseases, such as AD, PD, and T2DM. Conventional diagnosis is based on the appearance of fibrils or plaques, while neglects the role of early-stage oligomers in the disease progression. Recent studies have uncovered that it is the early-stage oligomer, rather than the mature fibril that contributes cytotoxicity. The formation of oligomers involves complicate structural conversions and it is essential to investigate their conformational changes for a better understanding of aggregation mechanism. The co-existence of soluble early-stage oligomers, intermediates, and pre-fibril species makes it difficult to be captured by morphological methods, and average structural information could be provided as they lack the ability of separation. Therefore, mass spectrometry (MS) becomes an alternative technique that presenting new and complementary insights into the onset of amyloid fibrils. This review highlights the hotspots and important achievements by MS in the field of amyloid formation mechanism, including the direct detection and differentiation of soluble oligomers (native MS), unambiguous identification of interacted sites involved in the onset of aggregation (HDX and CX), and conformational switch that leading to fibrilization (CCS regularity by IMS).